Recombinant Human Endostatin Suppresses Mouse Osteoclast Formation by Inhibiting the NF-κB and MAPKs Signaling Pathways - Chen, Nong; Gao, Ru-Feng; Yuan, Feng-Lai; Zhao, Ming-Dong (Frontiers in Pharmacology, 2016)
Rheumatoid arthritis is an autoimmune disease characterized by synovial hyperplasia and progressive joint destruction. As reported previously, recombinant human endostatin (rhEndostatin) is associated with inhibition of joint bone destruction present in rat adjuvant-induced arthritis; however, the effect of rhEndostatin on bone destruction is not known. This study was designed to assess the inhibitory effect and mechanisms of rhEndostatin on formation and function of osteoclasts in vitro, and to gain insight into the mechanism underlying the inhibitory effect of bone destruction. Bone marrow-derived macrophages isolated from BALB/c mice were stimulated with receptor activator of NF-κB ligand (RANKL) and macrophage colony-stimulating factor to establish osteoclast formation. Osteoclast formation was determined by TRAP staining. Cell viability of BMMs affected by rhEndostatin was determined using a MTT assay. Bone resorption was examined with a bone resorption pits assay. The expression of osteoclast-specific markers was analyzed using quantitative real-time PCR. The related signaling pathways were examined using a Luciferase reporter assay and western blot analysis. Indeed, rhEndostatin showed a significant reduction in the number of osteoclast-like cells and early-stage bone resorption. Moreover, molecular analysis demonstrated that rhEndostatin attenuated RANKL-induced NF-κB signaling by inhibiting the phosphorylation of IκBα and NF-κB p65 nuclear translocation. Furthermore, rhEndostatin significantly inhibited the activation of RANKL-dependent mitogen-activated protein kinases (MAPKs), such as ERK1/2, JNK, and p38. Hence, we demonstrated for the first time that preventing the formation and function of osteoclasts is an important anti-bone destruction mechanism of rhEndostatin, which might be useful in the prevention and treatment of bone destruction in RA.